Assessment of digital transformation challenges for business model innovation in the context of higher education institutions using a decision support approach - Gen Li; Xixiang Sun; Min Ye; Abbas Mardani (Journal of Innovation & Knowledge (JIK), 2024)
Higher education plays a central role in the current digital revolution. This sector is experiencing a constant process of digital transformation (DT) that is expected to produce substantial instabilities in the currently used business tools. However, the literature still lacks research investigating how the business tools are innovated from the perspective of 'higher education institutions (HEIs)' while considering the impact of DT on this process. To deal with the concern, this paper identifies the major impressions of DT on the business model provided by HEIs, using means of a fuzzy decision-making tool. To this end, the current paper integrated three previously-proposed methods, i.e., the 'intuitionistic fuzzy sets (IFSs)', the 'method based on the removal effects of criteria (MEREC)', the 'rank sum (RS)', and the 'additive ratio assessment (ARAS)' into a new decision-making framework called IF-MEREC-RS-ARAS. In the proposed hybrid method, IF-MEREC-RS is responsible for computing the objective-subjective weighting of the key DT challenges that arise for 'business model innovation (BMI)' in the perspective of HEIs. In addition, IF-ARAS evaluates the HEIs' preferences over various DT challenges for BMI in the context of HEIs. This research also involves an empirical case study for the assessment of the major DT challenges that arise for BMI in HEIs. To end, a number of comparisons and sensitivity discussions were carried out to compare the performance of the introduced model with that of other models. The findings confirmed the higher effectiveness of the developed model in terms of the tasks defined.
Keywords: A02; O32; C44; 650; Digital transformation; Higher education; Intuitionistic fuzzy sets; MEREC; ARAS; Rank sum weight; Multi-criteria decision-making